FACTORS AFFECTING CUSTOMER SATISFACTION IN 99 SPEEDMART STORE: A STUDY IN SEKSYEN 13, SHAH ALAM SELANGOR - Yusuf, Afifah Azzahra; Anuar, Aimi Binti; Azrin, Madam Khairunnisa Binti (Transpublika Publisher, 2024)
The Malaysian supermarket industry faces intense competition significant growth, necessitating an understanding of customer needs and preferences to achieve satisfaction and establish market leadership. Supermarket must prioritize key determinants of customer satisfaction, such as price, location, and store atmosphere, especially given the increased price sensitivity among Malaysian consumers. Therefore, gaining a comprehensive understanding of its determinants is crucial for researchers, retailers, and practitioners. This study’s current purpose is to empirical research the linking between price, location, and store atmosphere to customer satisfaction in supermarket industry among 99Speedmart Seksyen 13, Shah Alam. This study examined customer satisfaction in a specific locality enables a closer look at the factors influencing customer satisfaction. This study used a quantitative research approach to collect data from customers for this research. The researcher used a survey questionnaire to collect a sample size of 166 customers among 1956-Shah Alam Sek 13 (2) 99Speedmart which located in Jalan Boling Padang G13/G. This study used convenient sampling technique. The collected data used SPPS. The findings indicated that there is a notable correlation between price, location, and store ambiance and customer contentment in supermarkets. These outcomes could potentially aid supermarket managers in devising and executing more effective strategies to enhance customer relations and compete with rival stores.